Impact of Graft Material Type on Bone Regeneration Around Implants: A Case-Control Study - Awais Hussain, Anum Mahmood, Miral Shad, Muhammad Ali Akbani, Aisha Kousar, Sadaf Raffi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Bone regeneration around dental implants is a decisive factor for long-term osseointegration andfunctional stability. The choice of graft material has been debated, with autografts, allografts,xenografts, and synthetic substitutes offering distinct biological and mechanical advantages. This case–control study investigated